2022
DOI: 10.7759/cureus.27917
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and the Cardiovascular Disease: A Narrative Review

Abstract: Breast cancer is the most common malignancy affecting females worldwide and is also among the top causes of all cancer-related deaths. Cardiovascular disease (CVD) is known to have the highest rate of mortality in women. There are several risk factors for both CVD and breast cancer that overlap, such as diet, smoking, and obesity, and also the current breast cancer treatment has a significant detrimental effect on cardiovascular health in general. Patients with exposure to potentially cardiotoxic treatments, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…These findings underscore the importance of assessing cardiovascular risk factors in breast cancer patients, as these factors could potentially influence disease outcomes and treatment strategies. The prevalence of these risk factors in this study aligns with those of previous studies that have reported similar patterns of cardiovascular risk factors in breast cancer patients, indicating the consistency of these associations across different populations [15].…”
Section: Discussionsupporting
confidence: 90%
“…These findings underscore the importance of assessing cardiovascular risk factors in breast cancer patients, as these factors could potentially influence disease outcomes and treatment strategies. The prevalence of these risk factors in this study aligns with those of previous studies that have reported similar patterns of cardiovascular risk factors in breast cancer patients, indicating the consistency of these associations across different populations [15].…”
Section: Discussionsupporting
confidence: 90%
“…The risk for CTR-CVT is twice as high in survivors of several solid cancers and lymphoma compared with the general population (21)(22)(23). The long-term real-life data in this study reveal an even higher cumulative incidence after BC, with a cumulative CTR-CVT incidence of 71.8%.…”
Section: Discussionmentioning
confidence: 59%
“… 51 Breast cancer treatments, including trastuzumab targeted therapy, anthracycline-based chemotherapy, aromatase inhibitors, and radiation therapy (especially for left-sided breast cancer) can cause cancer therapy–related cardiac dysfunction. 52 , 53 …”
Section: Methodsmentioning
confidence: 99%